2019
DOI: 10.1039/c9nr02612f
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of ultrathin nanocellulose shells on tough microparticlesviaan emulsion-templated colloidal assembly: towards versatile carrier materials

Abstract: Ultrathin nanocellulose shells are constructed on the surface of polymer microparticles by an emulsion-templated self-assembly. The shell renders the microparticles biocompatible and highly dispersible in water with molecular recognition properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…This method enabled the loading of pH-responsive compounds, such as methylene blue, using polystyrene as a matrix. The carboxyl groups of the CNF shell showed pH-dependent properties and strong adsorption and drug release behavior [ 46 ]. Chemical or biological receptors can also be integrated to provide selectivity for sensing applications.…”
Section: Nanocellulose: Preparation Treatment Functionality and 3d Printabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This method enabled the loading of pH-responsive compounds, such as methylene blue, using polystyrene as a matrix. The carboxyl groups of the CNF shell showed pH-dependent properties and strong adsorption and drug release behavior [ 46 ]. Chemical or biological receptors can also be integrated to provide selectivity for sensing applications.…”
Section: Nanocellulose: Preparation Treatment Functionality and 3d Printabilitymentioning
confidence: 99%
“…Even though 3D-printable nanocellulose-based composites are still in their infancy, there has been an increase in their applications in different fields ranging from biomedicine, including wound dressing, drug release, and tissue engineering, sensors, food, and packaging, to energy storage and electronics, with growing interest in other areas as well [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ], summarized in Figure 6 . This section discusses the recent development in 3D-printed nanocellulose-based composites for food, environmental, food packaging, energy, and electrochemical applications.…”
Section: Applications Of 3d-printed Nanocellulose-based Materialsmentioning
confidence: 99%
“…Several studies on polymer composite preparation through Pickering emulsions have been reported, where nanocelluloses [22,23], microfibrillated lignocellulose [24], or chitin nanofibrils [25][26][27] were used as stabilizers. Furthermore, we report the synthesis of core-shell microparticles using this Pickering emulsion as a template [28].…”
Section: Introductionmentioning
confidence: 99%
“…was easily formed in water (Figure 11c). [ 166–172 ] The homogenous mixing was done free of any extra chemicals, such as surfactant or dispersant, just by employing a high shearing energy. [ 166–169,171 ] The nanocellulose‐covered resin droplets were retrieved after removing water by casting or vacuum‐filtration like a “paper‐making process.” The obtained “raw” nanocomposite films were further processed by hot‐compression to yield highly optically transparent (≈85% @ 4–25 wt% nanocellulose) and 3D‐moldable nanocomposite films.…”
Section: Nonmodification Interface Engineeringmentioning
confidence: 99%
“…[ 175,176 ] Also, by using Pickering‐stabilizing process, robust nanocellulose‐shell (ultrathin thickness of <50 nm) capsules were prepared that might find potential application in drug delivery and food applications. [ 170,177 ]…”
Section: Nonmodification Interface Engineeringmentioning
confidence: 99%